Genome-Wide Identification of Sorghum bicolor Laccases Reveals Potential Targets for Lignin Modification - Wang, Jinhui; Feng, Juanjuan; Jia, Weitao; Fan, Pengxiang; Bao, Hexigeduleng; Li, Shizhong; Li, Yinxin (Frontiers in Plant Science, 2017)
Laccase is a key enzyme in plant lignin biosynthesis as it catalyzes the final step of monolignols polymerization. Sweet sorghum (Sorghum bicolor (L.) Moench) is considered as an ideal feedstock for ethanol production, but lignin greatly limits the production efficiency. No comprehensive analysis on laccase has ever been conducted in S. bicolor, although it appears as the most promising target for engineering lignocellulosic feedstock. The aim of our work is to systematically characterize S. bicolor laccase gene family and to identify the lignin-specific candidates. A total of twenty-seven laccase candidates (SbLAC1-SbLAC27) were identified in S. bicolor. All SbLACs comprised the equivalent L1-L4 signature sequences and three typical Cu-oxidase domains, but exhibited diverse intron-exon patterns and relatively low sequence identity. They were divided into six groups by phylogenetic clustering, revealing potential distinct functions, while SbLAC5 was considered as the closest lignin-specific candidate. qRT-PCR analysis deciphered that SbLAC genes were expressed preferentially in roots and young internodes of sweet sorghum, and SbLAC5 showed high expression, adding the evidence that SbLAC5 was bona fide involved in lignin biosynthesis. Besides, high abundance of SbLAC6 transcripts was detected, correlating it a potential role in lignin biosynthesis. Diverse cis regulatory elements were recognized in SbLACs promoters, indicating putative interaction with transcription factors. Seven SbLACs were found to be potential targets of sbi-miRNAs. Moreover, putative phosphorylation sites in SbLAC sequences were identified. Our research adds to the knowledge for lignin profile modification in sweet sorghum.